(untitled) (Perner’s Contacts, 2011)
City public transport in the Czech Republic operates in all large cities. We recognize the subsystem bus, trolley bus, tram and subway - it is a special case, or other types integrated into the system of city public transport (eg. shipping, funicular, etc.). Critical areas in this article, we mean those areas that may negatively affect continuity and regularity of city public transport, in the worst case of its alone operation. We acquainted with the critical areas in the operation of city public transport which may negatively affect the passenger, the carrier, and the company that operates this type of transport.